Implementation And Challenges Of IFRS Convergence To PSAK In Writing Financial Statements Of Micro, Small, And Medium Enterprises (Msmes) In Indonesia - Taufiq, Maf’ul (Universitas Dehasen Bengkulu, 2025)
Financial statements serve as a crucial communication and informational tool, summarizing a company’s entire range of activities. Their existence plays a vital role for stakeholders in assessing potential business opportunities and allocating capital effectively. Although recognized internationally, Indonesia and most developing countries have gradually adopted the International Financial Reporting Standards (IFRS) into their national accounting standards. However, this adoption has not been fully embraced by business practitioners in Indonesia, particularly among Micro, Small, and Medium Enterprises (MSMEs). This study aims to examine the implementation of IFRS-based PSAK (Indonesian Financial Accounting Standards) by MSMEs in Indonesia, as well as the challenges and obstacles they encounter throughout the process. Using a sample of three MSME actors, the study finds that the primary challenges stem from limited knowledge and qualifications of human resources, the complexity of IFRS, and regulatory inconsistencies that lead to confusion.